2012
DOI: 10.1007/s00253-012-4343-2
|View full text |Cite
|
Sign up to set email alerts
|

Monosaccharide precursors for boosting chondroitin-like capsular polysaccharide production

Abstract: Chondroitin sulfate is a well-known bioactive molecule, widely used as an anti-osteoarthritis drug, that is nowadays mainly produced by animal tissue sources with unsafe extraction procedures. Recent studies have explored an integrated biotechnological-chemical strategy to obtain a chondroitin sulfate precursor from Escherichia coli K4 capsular polysaccharide, demonstrating the influence of environmental and growth conditions on capsule synthesis. In this research work, the flexibility of the strain biosynthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…CS is currently harvested from animal sources (cow, pig, shark, fish, and bird cartilage; Huskisson, ), but there is a growing interest in moving to sustainable microbial production platforms to minimize contamination and to control product consistency. One such production strategy involves harvesting a CS precursor from cultures of E. coli strains biosynthesizing a K4 capsule (Zanfardino et al ., ; Restaino et al ., , ; Schiraldi et al ., , ; Trilli et al ., ). This biotechnological relevance has provoked increased interest in improving biosynthesis of K4 CPS by manipulating E. coli metabolism (Restaino et al ., ; Cimini et al ., ; Cress et al ., ; Wu et al ., ).…”
Section: Chondroitinmentioning
confidence: 99%
See 1 more Smart Citation
“…CS is currently harvested from animal sources (cow, pig, shark, fish, and bird cartilage; Huskisson, ), but there is a growing interest in moving to sustainable microbial production platforms to minimize contamination and to control product consistency. One such production strategy involves harvesting a CS precursor from cultures of E. coli strains biosynthesizing a K4 capsule (Zanfardino et al ., ; Restaino et al ., , ; Schiraldi et al ., , ; Trilli et al ., ). This biotechnological relevance has provoked increased interest in improving biosynthesis of K4 CPS by manipulating E. coli metabolism (Restaino et al ., ; Cimini et al ., ; Cress et al ., ; Wu et al ., ).…”
Section: Chondroitinmentioning
confidence: 99%
“…One such production strategy involves harvesting a CS precursor from cultures of E. coli strains biosynthesizing a K4 capsule (Zanfardino et al ., ; Restaino et al ., , ; Schiraldi et al ., , ; Trilli et al ., ). This biotechnological relevance has provoked increased interest in improving biosynthesis of K4 CPS by manipulating E. coli metabolism (Restaino et al ., ; Cimini et al ., ; Cress et al ., ; Wu et al ., ). K4 CPS is similar in structure to unsulfated CS, with the exception of an acid labile, bisecting β‐fructofuranose attached to C3 of the GlcA residue (Fig.…”
Section: Chondroitinmentioning
confidence: 99%
“…In the first case CS is obtained enzymatically by in vitro chain elongation using UDP-sugar precursors and biotechnologically produced synthase enzymes. UDPglucose oxidized into UDP-glucuronic acid which promotes chondrogenesis and GAGs synthesis monosaccharides precursors help in boosting chondroitin-like capsular polysaccharide production [34,35], a hetero-oligomer complex of CS synthase-1 (CSS1)/chondroitin synthase-1 and CS synthase-2 (CSS2)/chondroitin polymerizing factor with the strongest polymerizing activity participate in the extension and initiation of CS [1]. In the other case CS is produced by using a biotechnological-chemical strategy consisting of three main steps: fermentative production of a chondroitin-like polysaccharide by capsulated bacteria, purification from the fermentation broth and then site specific chain sulphation.…”
Section: Productionmentioning
confidence: 99%
“…Recent studies have identified an imbalanced ratio between UDP-GalNAc and UDP-GlcA in E. coli K4 during growth, with GlcA being present in lower amounts [45]. This challenge was circumvented by adding GlcA and GalNAc monosaccharides to the medium at the beginning of growth, leading to a 64% increase in K4 CPS production [46]. Flux balance was also successfully addressed via a pfkA knockout in E. coli K4, favoring the production of fructose-6-phosphate.…”
Section: Chondroitinmentioning
confidence: 99%